Molecular biomarker-defined brain tumors: Epidemiology, validity, and completeness in the United States. Issue 11 (23rd April 2022) - Iorgulescu, J Bryan; Sun, Chuxuan; Neff, Corey; Cioffi, Gino; Gutierrez, Catherine; Kruchko, Carol; Ruhl, Jennifer; Waite, Kristin A; Negoita, Serban; Hofferkamp, Jim; Tihan, Tarik; McLendon, Roger; et al.
Abstract: Background: Selected molecular biomarkers were incorporated into the US cancer registry reporting for patients with brain tumors beginning in 2018. We investigated the completeness and validity of these variables and described the epidemiology of molecularly defined brain tumor types. Methods: Brain tumor patients with histopathologically confirmed diagnosis in 2018 were identified within the Central Brain Tumor Registry of the United States and NCI's Surveillance, Epidemiology, and End Results Incidence databases. The brain molecular markers (BMM) site-specific data item was assessed for coding completeness and validity. 1p/19q status, MGMT promoter methylation, WHO grade data items, and new ICD-O-3 codes were additionally evaluated. These data were used to profile the characteristics and age-adjusted incidence rates per 100 000 population of molecularly defined brain tumors with 95% confidence intervals (95% CI). Results: BMM completeness across the applicable tumor types was 75%-92% and demonstrated favorable coding validity. IDH-wildtype glioblastomas' incidence rate was 1.74 (95% CI: 1.69-1.78), as compared to 0.14 for WHO grade 2 (95% CI: 0.12-0.15), 0.15 for grade 3 (95% CI: 0.14-0.16), and 0.07 for grade 4 (95% CI: 0.06-0.08) IDH-mutant astrocytomas. Irrespective of WHO grade, IDH mutation prevalence was highest in adolescent and young adult patients, and IDH-mutant astrocytomas were more frequently MGMT promoter methylated. Among pediatric-type tumors, the incidence rate was 0.06 for H3K27M-mutant diffuse midline gliomas (95% CI: 0.05-0.07), 0.03 for SHH-activated/ TP53 -wildtype medulloblastomas (95% CI: 0.02-0.03), and <0.01 for both C19MC-altered embryonal tumor with multilayered rosettes and RELA -fusion ependymomas. Conclusions: Our findings illustrate the success of developing a dedicated, integrated diagnosis variable, which provides critical molecular information about brain tumors related to accurate diagnosis.